Nonlinearity effect on the dynamic behavior of the clayey basin edge - Khanbabazadeh, Hadi (Techno-Press, 2024)
Investigations has shown that the correct estimation of the effective amplification period is as important as the amplification value itself. It gets more important in 2D basins. This study presents a quantitative coefficient for consideration of the nonlinearity effect in terms of amplification value and the shift in its period which is missing or ineffectively considered in the previous studies. To attain this goal, by the application of a time domain fully nonlinear method, the deviation of the more common equivalent linear results from the basin nonlinear behavior under strong ground motions is investigated quantitatively. Also, despite the increase in the damping ratio, the possibility of the increase in the amplification due to the increase in motion strength is shown. To make the results useful in engineering practice, by introducing nonlinearity ratio, the effect of the nonlinearity is quantitatively estimated for two soft and stiff clayey basins with three different depths under a set of motions scaled to two target spectrum. Results show that at the 100 m depth soft clayey basin, while the nonlinearity ratio shows a 35% deviation at the basin edge part under DD1 motion level, its effect moves to the central part with 20% effect under DD3 motion level. By the increase in depth to 150 m, the results show a decrease in the overall effect of the nonlinear behavior for both clay types. At this depth, the nonlinearity ratio gives a 30% and 17% difference on a limited distance from outcrop at the soft clayey basin under DD1 and DD3 motion levels, respectively. At the 30 m depth basins, the nonlinearity ratio shows up to 25% difference for different cases. The presented ratio would be introduced as nonlinearity coefficients for consideration of the nonlinearity effects in the codes. The presented quantitative margins will help the designer to have a better understanding of the amplification period change because of nonlinearity over 2D basin surface.
Keywords: basin edge; dynamic behavior; ground motion; nonlinear behavior; numerical modeling; site effect